T cell receptor excision circles are potential predictors of survival in adult allogeneic hematopoietic stem cell transplantation recipients with acute myeloid leukemia - Söderström, Anna; Vonlanthen, Sofie; Jönsson-Videsäter, Kerstin; Mielke, Stephan; Lindahl, Hannes; Törlén, Johan; Uhlin, Michael (Frontiers in Immunology, 2022)
Background: Lymphocyte neogenesis from primary lymphoid organs is essential for a successful reconstitution of immunity after allogeneic hematopoietic stem cell transplantation (HSCT). This single-center retrospective study aimed to evaluate T cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC) as surrogate markers for T and B cell recovery, as predictors for transplantation-related outcomes in adult acute myeloid leukemia (AML) patients. Methods: Ninety adult patients diagnosed with AML and treated with HSCT between 2010 and 2015 were included in the study. TREC and KREC levels were measured by quantitative PCR at 1, 3, 6, and 12 months after transplantation. Results: Overall, excision circle levels increased between 3 and 6 months post-HSCT for TREC (p = 0.005) and 1 and 3 months for KREC (p = 0.0007). In a landmark survival analysis at 12 months post-HSCT, TREC levels were associated with superior overall survival (HR: 0.52, 95% CI: 0.34 - 0.81, p = 0.004). The incidence of viral infections within the first 100 days after transplantation was associated with lower TREC levels at 6 months (p = 0.0002). CMV reactivation was likewise associated with lower TREC levels at 6 months (p = 0.02) post-HSCT. KREC levels were not associated with clinical outcomes in statistical analyzes. Conclusions: Results from the present study indicate that TREC measurement could be considered as part of the post-HSCT monitoring to identify AML patients with inferior survival after transplantation. Further prospective studies are warranted to validate these findings.